Diabetes mellitus influences the expression of NPY and VEGF in neurons of rat trigeminal ganglion. (April 2017) - Jerić, Milka; Vukojević, Katarina; Vuica, Ana; Filipović, Natalija
Abstract: Background: Diabetes mellitus (DM) influences the trigeminal nerve function by changing the pain response and transduction of the orofacial sensory pathways. It affects the inflammatory response via neuropeptide Y (NPY) and vascular endothelial growth factor (VEGF), which could potentially have a relevant role in the pathophysiology of diabetic neuropathy. The aim was to investigate expression of VEGF and NPY in subpopulations of trigeminal ganglion (TG) neurons in rat models of early DM1 and DM2. Methods: DM1 model was induced by an intraperitoneal (i.p.) injection of streptozotocin (STZ) (55 mg/kg). DM2 rats were fed with a high fat diet (HFD) for two weeks and then received 35 mg/kg of STZ i.p. Two weeks and 2 months after the STZ-diabetes induction, rats were sacrificed and TG was immunohistochemically analyzed for detection of VEGF and NPY expression, and also double immunofluorescence labeling with isolectin (IB4) was completed. Results: An increased percentage of NPY+ neurons was observed 2 weeks after DM1 and 2 months post DM2 induction. NPY immunoreactivity was restricted to IB4-negative small-diameter and IB4+ neurons. Two weeks post induction, DM1 rats showed an increased percentage of VEGF/IB4− large neurons and DM2 rats showed an increased percentage of VEGF/IB4+ neurons. Two months after DM induction, the DM1 group showed a reduced percentage of VEGF/IB4 − small neurons. Conclusion: The observed changes may play a critical role in the modulation of nociceptor activity and plasticity of primary sensory trigeminal neurons. The results contribute to the understanding of the basic pathophysiology of trigeminal diabetic neuropathy. Highlights: DM1 and DM2 cause increased expression of NPY in neurons of the rat trigeminal ganglia. Expression of NPY is increased in nociceptive small IB4 − and IB4 + neurons. Two-week DM1 and DM2 cause increased expression of VEGF in neurons of the rat TG. VEGF expression increases in different populations of neurons in DM1 and DM2. Expression of VEGF is decreased two months after DM1 and DM2 induction.